A social identity analysis of technological innovation in an action sport: judging elite half-pipe snowboarding - Harding, J.; Lock, D.; Toohey, K. (European Sport Management Quarterly, 2016)
Research question: We explore how facets of the group identity shared by elite half-pipe snowboarding (EHPS) constituents (i.e. judges, athletes, and coaches) shape attitudes towards a proposed technological innovation to the existing judging process.